(3XGgQI GdJQJH ai GddZI GdYQHjI (B: s (3OQGSI ai GdJQcjH h GdOdGdI (B/ s - (3YHOGdQMef QHjY SjO s; (3Wg eMeO YhV Gddg GdLfOi (B: s ((3GdbGgQI (B: s (3YHOGdQMef QHjY SjO (B: s, 2013)
(3jJfGhd gPG GdHMK XGgQI dZhjI OdGdjI h gi GdJQJH h CYfi Hg JQJH GdYfGUQ GddZhjI Ydi HYVgG GdHYV eKd JQJH GdaGYd Ydi GdaYd h JQJH GdNHQ Ydi GdeHJOC h GdJQJH dg eSJhjGJ eJYOOI agfGc JQJH Ydi GdeSJhi GdUhJi h gfGc JQJH Ydi GdeSJhi GdUQai h gfGc JQJH Ydi GdeSJhi GdJQcjHi h GdOdGdi h GdJQJH Ydi GdeSJhi GdJQcjHi bO jchf Hjf GdeaQOGJ h HYVgG h jSei JQJH GdeaQOGJ h bO jchf Hjf LedJjf Ch CcKQ h jSei JQJH GdLed h bO JQcR GdHMK Ydi GdeSJhi GdJQcjHi h GdOdGdi ddJQJH ef NdGd fehPLjf CMOgeG dJQJH GdeaQOGJ h gh GdLedI GdaYdjI h GdBNQ dJQJH GdLed h gh CSdhH GdTQW h aUdJ GdMOjK ai NUGFUgeG GdJQcjHjI h GdOdGdjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdfMh h GdUQa h GdYQhVs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJQJH s; (3GdJbOje s; (3GdRjGOI s